2012
DOI: 10.1007/s00382-012-1438-5
|View full text |Cite
|
Sign up to set email alerts
|

Multidecadal variability in local growing season during 1901–2009

Abstract: Global warming exerts a lengthening effect on the growing season, with observational evidences emerging from different regions over the world. However, the difficulty for a global overview of this effect for the last century arises from limited availability of the long-term daily observations. In this study, we find a good linear relationship between the start (end) date of local growing season (LGS) and the monthly mean temperature in April (October) using the global gridded daily temperature dataset for 1960… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 50 publications
4
28
1
Order By: Relevance
“…The present study shows a historical perspective of changes in growing season in China. Xia et al (2013) found that multidecadal variability in LGS indices could be linked to the Atlantic Multidecadal Oscillation (AMO), which is expressed as the multidecadal variations of the North Atlantic sea surface temperature with a period of about 65−80 years and amplitude of 0.4°C (Schlesinger and Ramankutty 1994;Trenberth and Shea 2006). They suggested that the AMOrelated multidecadal variability accelerates the lengthening of LGS in the Northern Hemisphere by about 53% for the last three decades.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The present study shows a historical perspective of changes in growing season in China. Xia et al (2013) found that multidecadal variability in LGS indices could be linked to the Atlantic Multidecadal Oscillation (AMO), which is expressed as the multidecadal variations of the North Atlantic sea surface temperature with a period of about 65−80 years and amplitude of 0.4°C (Schlesinger and Ramankutty 1994;Trenberth and Shea 2006). They suggested that the AMOrelated multidecadal variability accelerates the lengthening of LGS in the Northern Hemisphere by about 53% for the last three decades.…”
Section: Discussionmentioning
confidence: 99%
“…The Ds (De) shows an advancing (delaying) rate of about −2.0 (1.5) days per decade for the period 1965−2012, leading to a lengthening of LGS with a rate of about 3.5 days per decade. et al 2011 ;Xia et al 2013). EEMD is also efficient for obtaining the long-term trend and multidecadal variability component in the climate series , which are focused on by the present study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations